MULTI ATTRIBUTE DECISION MAKING DENGAN METODE TECHNIQUE FOR ORDER PREFERENCE BY SIMILARITY TO IDEAL SOLUTION UNTUK MENENTUKAN REKOMENDASI PENERIMA BEASISWA BBM DAN PPA DI STMIK AMIKOM PURWOKERTO - Fandy Setyo Utomo (Telematika, 2010)
Multi Attribute Decision Making Model with Method Technique For Order Preference By Similarity To Ideal Solution for determining recommendations grantee is one application of the Decision Support System (DSS). This application is designed to help the management to determine STMIK AMIKOM Purwokerto recommendation Bantuan Belajar Mahasiswa (BBM) recipients and Peningkatan Prestasi Akademik (PPA). With this application, it is expected the process of determining the scholarship recipients recommendations become more effective and efficient in terms of data processing.